Deskripsi Pelaksanaan Pendidikan Karakter Jujur Dan Disiplin Dalam Pembelajaran Siswa Kelas V SD Negeri 17 Pontianak Kota - Ilham Nur Mardiyanto; Hairida Hairida; Agung Hartoyo (Journal on Education, 2025)
This research aims to describe how the implementation of the implementation of honest and disciplined characters as well as the obstacles and solutions in learning for students in grade V of SD Negeri 17 Pontianak Kota by describing the implementation, obstacles, and solutions to the obstacles in the implementation of honest and discipline. The research used a qualitative approach with the data obtained will be analyzed based on facts in the field, therefore this type of research is qualitative descriptive research. This research is a qualitative descriptive research. Data collection techniques data collection techniques used, namely observation, interviews, and documentation with the object of research are students, teachers, and other school parties. The objects of research are students, teachers, and other school parties. Research results after data collection, data reduction, data presentation, until analysis showed that the implementation of honest and disciplined characters in learning in class V of SD Negeri 17 Pontianak Kota has been implemented based on research using five indicators of honesty and discipline. based on research using five honest indicators and four indicators of discipline. In its implementation, there are obstacles that occur due to internal factors from the students themselves and external factors, namely the role of teachers, principals, and parents. the role of teachers, principals, and parents in the effort to implement the character of honesty and discipline.